2022
DOI: 10.1177/09697330211043273
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of critical care nurses during the early months of the COVID-19 pandemic

Abstract: Background: Critical care nurses have risked their lives and in some cases their families through hazardous duty during the COVID-19 pandemic and have faced multiple ethical challenges. Research/aim: The purpose of our study was to examine how critical care nurses coped with the sustained multi-faceted pressures of the critical care environment during the unchartered waters of the COVID-19 pandemic. It was anticipated that our study might reveal numerous ethical challenges and decision points. Research design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Fear of the unknown dominated the ICU nurses and ICU management when new knowledge kept evolving how they operate in their role. A study that looked at the experiences of ICU nurses during the COVID-19 pandemic by Moore et al (2022) in the United States revealed that ICU nurses felt unsafe and feared for their lives while providing care for the COVID-19 infected patients. They were uncertain if the N95 masks are a http://www.curationis.org.za Open Access sufficient infection and prevention measure, as the pandemic progressed there was an exacerbation of limited personal protective equipment (PPE), which increased the feeling of being unsafe and putting their lives at risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of the unknown dominated the ICU nurses and ICU management when new knowledge kept evolving how they operate in their role. A study that looked at the experiences of ICU nurses during the COVID-19 pandemic by Moore et al (2022) in the United States revealed that ICU nurses felt unsafe and feared for their lives while providing care for the COVID-19 infected patients. They were uncertain if the N95 masks are a http://www.curationis.org.za Open Access sufficient infection and prevention measure, as the pandemic progressed there was an exacerbation of limited personal protective equipment (PPE), which increased the feeling of being unsafe and putting their lives at risk.…”
Section: Introductionmentioning
confidence: 99%
“…They were uncertain if the N95 masks are a http://www.curationis.org.za Open Access sufficient infection and prevention measure, as the pandemic progressed there was an exacerbation of limited personal protective equipment (PPE), which increased the feeling of being unsafe and putting their lives at risk. In addition to their frustration, knowledge as to how COVID-19 is transmitted and the disease process and treatment was questioned, which led to changes in infection control policies, treatment and nursing care measures in the ICU (Moore et al 2022). A cross-sectional study conducted in China showed that in the first wave of COVID-19 there were about 32% of ICU nurses had direct exposure to COVID-19 (Chegini et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nurses have difficulties navigating the contradictory needs for both closeness to and distance from patients. Similar to many people during the pandemic, nurses experience an unpredictable future and feelings of worry and insecurity [ 2 , 3 , 4 , 5 ]. Several studies show that many nurses experience work-related stress and multiple psychological stressors during the pandemic, leading to burnout [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many people during the pandemic, nurses experience an unpredictable future and feelings of worry and insecurity [2][3][4][5]. Several studies show that many nurses experience work-related stress and multiple psychological stressors during the pandemic, leading to burnout [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%